2019
DOI: 10.2147/jmdh.s201155
|View full text |Cite
|
Sign up to set email alerts
|

<p>Are dental care providers in Saudi Arabia prepared to treat patients with special needs?</p>

Abstract: Background: Equity in services accessibility is one of the major components of good quality healthcare. However, patients with special needs have limited access to dental care services, which could be due to the lack of training and experience of the dental care providers that might effect on their preparedness and willingness when it comes to caring for the patients with special needs. Objectives: The main objective of this study is to determine the factors influencing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 16 publications
(10 reference statements)
2
17
0
Order By: Relevance
“…The dental health services in the Kingdom have undergone a huge transformation in the last two decades. Dental services provided by the Saudi Arabian Ministry of Health (MOH) are provided at no cost to the patient (Alumran et al, 2019). On the other hand, there is no system in place for routine dental checkups, and dentists are not obliged to keep a record of their patients for monitoring purposes (Baghdadi et al, 2011).…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
“…The dental health services in the Kingdom have undergone a huge transformation in the last two decades. Dental services provided by the Saudi Arabian Ministry of Health (MOH) are provided at no cost to the patient (Alumran et al, 2019). On the other hand, there is no system in place for routine dental checkups, and dentists are not obliged to keep a record of their patients for monitoring purposes (Baghdadi et al, 2011).…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
“…There is growing advocacy in Australia and internationally to improve the training of oral health professionals to ensure the dental workforce appreciates the needs of these individuals and has the skills to confidently address them 2,11–18 . However, little is known of what clinicians find challenging about managing this group of individuals and whether additional support would improve their willingness to treat those with special needs 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature review, patients with special needs are more likely to have poor oral hygiene and oral diseases for numerous reasons, including limited dental-care access [37]. Aljabri et al [38] reported that 15.5% of individuals with special needs have an issue with accessibility to dental services [39].…”
Section: Resultsmentioning
confidence: 99%